Experiment Degree Heating Week (eDHW) as a novel metric to reconcile and validate past and future global coral bleaching studies. (1st January 2022) - Leggat, William; Heron, Scott F.; Fordyce, Alexander; Suggett, David J.; Ainsworth, Tracy D.
Abstract: Coral bleaching has increasingly impacted reefs worldwide over the past four decades. Despite almost 40 years of research into the mechanistic, physiological, ecological, biophysical and climatic drivers of coral bleaching, metrics to allow comparison between ecological observations and experimental simulations still do not exist. Here we describe a novel metric – experimental Degree Heating Week (eDHW) – with which to standardise the persistently variable thermal conditions employed across experimental studies of coral bleaching by modify the widely used Degree Heating Week (DHW) metric used in ecological studies to standardise cumulative heat loading. Highlights: We propose a novel metric (eDHW) to allow comparison of coral bleaching experiments. Analysis of 62 studies from 38 locations verify this novel metric can explain bleaching outcomes. eDHWs provide a means to compare and standardise bleaching conditions in experimental studies. eDHWs can guide development of experimental protocols to better replicate local conditions.